O Jorubo e o Meriri Ikureu Oiagodu Rogu: encontro intercultural e poder entre os Bororo da Aldeia Meruri - Oliveira, Eloir Inácio de (2017)
The present research refers to a historical, anthropological, religious and political-social study on the exercise of the traditional power structures of the Bororo People, their great changes throughout history, how it organizes itself today and its approximation with the indigenous movement in the context of the struggles of Brazilian popular movements. The Meruri Village, located in the municipality of General Carneiro (MT), was selected as the study space. The long 114-year coexistence between Bororo and Salesian missionaries brought about unique changes in the exercise of indigenous power. But these were not in a relationship of authoritarianism or oppression. Even with the effects of the positivist mentality of the earliest times, adaptations and resignifications were established, culminating in a unique alliance that reached the symbol of the shed blood. The comparison of power in the traditional village with that of the present one shows that the figures of power have changed, but the main source of authority remains the same: society itself as a whole